Tinjauan Aspek Metabolik Vitamin A - Zainal Arifin Nang Agus, Zainal Arifin Nang Agus (Universitas Gadjah Mada, 1985)
Vitamin A deficiency canoccur not only from inadequate intake but also because of poor in testinal absorption or inadequate conversion of provitamin A, as occurs in diseases of the liver or malnutrition. It has recently been reported that Zinc, Vitamin E and Vitamin C are necessary to-maintain normal concentrations of vitamin A in the plasma. Hypervitaminosis A may occur as a consequence of the administration of large doses of vitamin A concentrates. Vitamin A toxicity causes increases in levels of lipids, glycogen and citrate in the liver. As important therapeutic for vitamin A deficiency, supplementations of protein, lipid, Zinc, Vitamin E and vitamin C increase the efficacy of vitamin A therapy. Key Words: vitamin A deficiency - malnutrition - xerophthalmia - carotene - hypervitaminosis